Clinical and morphological characteristics with markers of reparation in neuropathic diabetic foot ulcers. - Elena Yurievna Komelyagina (Endocrinology Research Centre, 2015)
Aim. To compare the clinical and morphological characteristics of chronic diabetic foot ulcers and the markers of repair.Materials and Methods.We included 26 patients with neuropathic diabetic foot syndrome who had signs of severe peripheral neuropathy. Biopsies were performed from the margin and central part of the lesion and were fixed in a 10% formalin solution before being placed on paraffin slides and stained with hematoxylin and eosin. We assessed the percentages of necrotic, granulation and fibrotic tissues and the severity of vascular hyalinosis. Immunohistochemistry was performed with initial antibodies to Ki-67 (a marker of proliferation), smooth muscle actin (a marker of myofibroblast synthesis) and cytokeratin (a marker of epithelisation). For analysis, the samples were divided into three groups by the length of time the ulcer had been present: group 1 (≤90 days; 9 samples), group 2 (91–365 days; 10 samples) and group 3 (>365 days; 9 samples).Results. The patients of group 3 were older than those of groups 1 and 2 (53.7±2.7 vs 51.7±5.9 vs 59.9±5.6 years; p=0.04). There were no differences in the duration of diabetes, glycated haemoglobin or severity of neuropathy. The percentage of necrotic tissue was higher in group 1 (33.7%±21.7% vs 11.0%±3.9% vs 12.8%±6.1%; p=0.02) and the percentage of fibrotic tissue was highest in group 3 (21.1%±21.0% vs 35.5%±19.8% vs 54.4%±23.9%; p=0.001). However, the amount of granulation tissue was not different between the groups (45.2%±21.1% vs 53.5%±21.1% vs 32.8%±26.3%; p=0.4). There was also no difference in the severity of vascular hyalinosis between the groups (p=0.9). Expression of Ki-67 was higher in groups 1 and 2, implying a greater capacity to regenerate. The expression of smooth muscle actin and cytokeratin was higher in groups 1 and 2 but without statistical significance.Conclusion. The morphological characteristics and regenerative capacities of neuropathic diabetic foot ulcers differ with the duration the ulcer has been present. Patients with ulcers for less than 1 year were characterised by higher cell proliferation but lower fibrosis. Neuropathic diabetic foot ulcers that are unable to heal over a year are characterised by incomplete regeneration and higher levels of fibrosis. Thus, different treatment approaches are needed depending on how long an ulcer has been present.